The language-mind interface in psycholinguistics: A systematic literature review and cross-disciplinary synthesis - Budianto Hamuddin; Dessi Natalia; Meutya Rizki Ramadhani; Fatma Setya Ningrum; Alexsander Yandra (Journal on English as a Foreign Language, 2026)
While psycholinguistic research has advanced significantly, gaps persist in understanding how linguistic diversity, bilingualism, and socio-emotional factors influence cognitive mechanisms in language processing, particularly beyond monolingual and Western contexts. This study aims to address these gaps by conducting a systematic literature review of 24 peer-reviewed articles published between 2019 and 2024. Utilizing a structured analytical framework – PRISMA, the study synthesizes findings on the roles of working memory, executive functions, and neural structures in language acquisition and processing. The results highlight that bilingualism enhances executive control and cognitive flexibility, yet methodological inconsistencies and limited representation of non-Western linguistic contexts remain challenges. Additionally, the integration of neuroimaging, artificial intelligence, and interdisciplinary approaches is emphasized as a means to develop more comprehensive models of language cognition. The study has practical implications for bilingual education, language therapy, and AI-driven linguistic analysis, with broader contributions to cognitive science, language policy, and cross-cultural communication. By bridging linguistic, psychological, and neuroscientific perspectives, this research advances the field of psycholinguistics. It underscores the need for culturally adaptive, technology-integrated methodologies to inform education, healthcare, and global communication strategies.